Letter to the Editor Carotid artery Stenting is not an alternative to Surgery - Kamil Hasan Tüzün; Şakir Arslan; Erkan Köklü; İsa Öner Yüksel; Göksel Çağırcı; Nermin Bayar; Akar Yılmaz; Görkem Kuş; Nurgül Yılmaz; Yasemin Biçer Gömceli; Bekir Erol (KARE Publishing, 2014)
According to the recent studies it is clear that carotid artery stenting carries higher risk for major and minor strokes. Therefore it is not an alternative treatment to surgery in symptomatic patients. For asymptomatic patients the beneficial role of surgery and stenting is still under discussion.